QUESTIONS REGARDING THE APPOINTMENT AND EXECUTION OF FORENSIC EXAMINATIONS IN THE PROCESS OF JUDICIAL PROCEEDINGS (World Bulletin of Management and Law, 2024)
The article examines the procedural order of conducting forensic examinations during judicial investigation.
Keywords: Evidence; Expertise; Court